Political Essay on the Kingdom of New Spain: Humboldt and the history of Mexico - Fernandes, Luiz Estevam O. (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2014)
AbstractIn this paper we discuss how Alexander von Humboldt conceived a past to New Spain in his Political Essay on New Spain (1811) and how this text was, in turn, appropriated by the Mexican historiography during the 19th century. In order to do so, we analyze how the Prussian drew from American sources, particularly from the text of the Jesuit Francisco Javier Clavijero, written shortly before. We also study Humboldt’s conceptions of text and of history, highlighting the place of the indigenous in the composition of his reasoning. Finally, we give examples of how the Mexican nationalist historiography read and reinterpreted the Political Essay. ResumenEn este artículo se discute cómo Alexander von Humboldt concibió un pasado a la Nueva España en su Ensayo político sobre el reino de la Nueva España (1811) y cómo este texto, a su vez, fue apropiado por la historiografía mexicana durante el siglo XIX. Para ello, se analiza cómo el prusiano se ha valido de fuentes americanas, sobre todo a partir del texto del jesuita Francisco Javier Clavijero, escrito poco antes. También estudiamos las concepciones de texto y de la historia de Humboldt, destacando el lugar de los indígenas en la composición de su razonamiento. Por último, damos ejemplos de cómo la historiografía nacionalista mexicana leyó y reinterpretó el Ensayo político. RésuméCet article explique comment Alexander von Humboldt a conçu une passé pour la Nouvelle-Espagne dans son Essai politique sur le royaume de la Nouvelle-Espagne (1811) et la façon que ce texte, à son tour, a été approprié par l’historiographie mexicaine au cours du XIXe siècle. Ainsi, nous analysons comment le prussien a utilisé des sources américaines, en particulier le texte du jésuite Francisco Javier Clavijero, écrit un peu de temps avant. Nous étudions également les conceptions de texte et de l’histoire de Humboldt, en soulignant la place des indigènes dans la composition de son raisonnement. Enfin, nous donnons des exemples de la façon dont l’historiographie nationaliste mexicain a lu et a réinterprété l’Essai politique.